2022
DOI: 10.3899/jrheum.211017
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Virtual Care: A Consensus Statement From the Canadian Rheumatology Association

Abstract: Objective To develop best practice statements for the provision of virtual care in adult and pediatric rheumatology for the Canadian Rheumatology Association's (CRA) Telehealth Working Group (TWG). Methods Four members of the TWG representing adult, pediatric, university-based and community rheumatology practices defined the scope of the project. A rapid literature review was conducted between April-May 2021 of existing systematic reviews, policy documents and published literature and abstracts on the topic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…Musculoskeletal specialties Barber et al (2022) • "Rheumatologists should adhere to national recommendations on best practices, and provincial standards and regulations for virtual care, including licensing considerations, patient privacy, confidentiality, documentation, and consent.…”
Section: Guideline Development Group (Year) Recommendations Standards...mentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal specialties Barber et al (2022) • "Rheumatologists should adhere to national recommendations on best practices, and provincial standards and regulations for virtual care, including licensing considerations, patient privacy, confidentiality, documentation, and consent.…”
Section: Guideline Development Group (Year) Recommendations Standards...mentioning
confidence: 99%
“…Wahezi et al, 2020 reported on a reference guide for musculoskeletal and neurologic examination that can be used in telemedicine practice. Barber et al, 2022, who included a rapid literature review and a subsequent Delphi process, reported on quality and patient safety considerations when developing the best practice statements for rheumatology virtual care. The recommendations from those articles are listed in Table 5.…”
Section: Previous Cadth Reportsmentioning
confidence: 99%
“…Affleck (2022: 40) makes a forceful call for "greater definitional and taxonomic rigour and the support of an established equity framework" to better address digital health equity. In their consensus statement on best practices for virtual care, the Canadian Rheumatology Association applied an equity lens to identify 10 equity-related factors and associated considerations for the decision making on virtual care versus in-person care (Barber et al 2022). Equitable access to high-quality healthcare, whatever the mode, is important, but the issue is broader.…”
Section: Digital Health Equitymentioning
confidence: 99%
“…In his 2021 paper, Falk called for specialty societies to develop specialty-specific guidelines, and the Canadian Medical Protective Association (CMPA) supports this call in a recent White Paper (CMPA 2022; Falk 2021). The Canadian Rheumatology Association took an interesting approach to this in its 2022 consensus statement (Barber et al 2022). It classified seven reasons for the clinical encounter, ranging from reviewing test results to undifferentiated disease, and assessed them against clinical considerations, type of virtual care available and preference and access considerations.…”
Section: Appropriatenessmentioning
confidence: 99%
“… 105 All these advancements might need standard frameworks and regulations as well as manuals for rheumatology practitioners to act in a legal, best-practice, and financially reimbursed space. 106 In particular for mhealth tools like apps for monitoring of symptoms and impact of disease clinics and investigators have tested different concepts for use in clinical care and connection to their registers. App-based assessment is similarly accepted by patients as completing PRO measures in the clinic, a discussion about the patient scores on PROs may even improve the patient-physician relationship.…”
Section: Introductionmentioning
confidence: 99%